Beyond the tropicalization of concepts: theorizing digital realities with and from the Global South (introduction to a special issue) - Gómez Cruz, Edgar (2023)
In this introductory section of the special issue titled “Beyond the Tropicalization of Concepts: Theorizing Digital Realities With and From the Global South,” the editors present a critical examination of the unquestioned adoption of theoretical frameworks from dominant regions of power and knowledge in the context of the Global South. This process, referred to as the “tropicalization of concepts,” is scrutinized for its consequences, which include the unequal significance of concepts, the naturalization of certain realities, the one-sided flow of ideas, and their solidification in public policies. In response to these challenges, the eight articles included in this special issue contribute valuable insights into innovative approaches for studying, theorizing, and engaging with the unique digital realities of the Global South. These articles shed light on diverse aspects of digital media use in different regions and offer fresh perspectives on how to conceptualize and address the associated issues.